Organizational reforms and gender: Feminization of middle management in Finnish and German banking - Janne Tienari; Sigrid Quack; Hildegard Theobald (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
In this article, we analyze the longitudinal relationship between organizational reforms (with downsizing elements) and feminization of a specific managerial position. We maintain that two dominant contemporary approaches to reforms and change, i.e. the managerialist literature and its socio-political criticisms, have predominantly been gender-blind. We argue that the unfolding of organizational reforms in bureaucratic business firms cannot fully be understood without reference to how managerial jobs are redefined in relation to each other, and to what are the gendered connotations involved and the type of workforce sought for the newly defined jobs. These gendered demands of reforms must, moreover, be addressed in association with what comes to be seen as the adequate (female and male) supply by top decision-makers. We contend that the gendered patterns inherent in organisational reform can only be discerned if the research takes into account the ways in which reforming is intertwined with developments in the division of labour between men and women, power and authority relations, and norms and values prevalent in the proximate business environment and the society at large. This leads us to suggest analysis which identifies processes of organising as constructed under, but not fully determined by, specific spatial and temporal conditions of gendered social practice. We present in-depth evidence from organizational reforming in two banks, located in societies with significantly divergent gender cultures and gender orders (i.e. Finland and Germany). Through a detailed cross-national comparison, we propose a common fundamental operating mechanism for the reformgender link, and specify a number of societal differences in form. In general, our evidence supports the argument that specific forms of restructuring - even with reductive elements - in fact promote feminization of middle management positions, albeit as a reflection of a development that reproduces gender segregation in new forms. – – In diesem Beitrag wird der Zusammenhang zwischen Organisationsreformen und der Feminisierung einer spezifischen Managementposition aus einer Langzeitperspektive analysiert. Den Ausgangspunkt bildet eine Kritik an derzeit dominierenden Erklärungsansätzen zum Organisationswandel. Sowohl die managementorientierte Literatur als auch ihre sozialwissenschaftliche Kritik schenken deren geschlechtsspezifischen Implikationen zumeist keine Aufmerksamkeit. Wir gehen hingegen davon aus, daß der Verlauf von Organisationsreformen in bürokratischen Unternehmen nicht ohne Einbezug der Neudefinition des Verhältnisses von Leitungspositionen zueinander einschließlich der damit verbundenen geschlechtsspezifischen Konnotationen und des von SpitzenmanagerInnen gewünschten Typus von (weiblichem und männlichem) Personal für die neu-definierten Positionen verstanden werden kann. Eine Untersuchung der sich im Verlauf von Organisationsreformen entwikkelnden geschlechtsspezifischen Muster erfordert die Berücksichtigung der Arbeitsteilung zwischen Männern und Frauen, der Beziehungen zwischen Macht und Autorität sowie der Normen und Werte innerhalb der Unternehmen und der Gesellschaft insgesamt. Notwendig werden Analysen, die Organisationsveränderungen als durch räumlich und zeitlich definierte, geschlechtsspezifische soziale Praktiken konstruiert, aber nicht völlig determiniert, begreifen. Die vorliegende Untersuchung basiert auf Fallstudien in zwei Banken, die in Ländern - Deutschland und Finnland - mit sehr unterschiedlichen Geschlechtersystemen angesiedelt sind. Die Ergebnisse des Vergleichs deuten darauf hin, daß Organisationsreform und geschlechtsspezifische Implikationen in beiden Ländern durch einen ähnlichen Mechanismus miteinander verknüpft sind. Hingegen werden Form und Verlauf der Reformprozesse durch das jeweilige länderspezifische Geschlechtersystem geprägt. Die Ergebnisse zeigen, daß spezifische Formen der Restrukturierung - und zwar auch im Kontext einer Personalreduktion - durchaus die Feminisierung einer Managementposition fördern können. Dies geht aber mit der Herausbildung neuer Formen der Geschlechtersegregation einher.
Keywords: 330; Bank; Reorganisation; Geschlecht; Weibliche Führungskräfte; Finnland; Deutschland